KEBIJAKAN NON PENAL PENGGUNAAN SENJATA API DIKAITKAN DENGAN PENYALAHGUNAAN SENJATA API OLEH ANGGOTA POLRI - Putri, Lia Novita; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Crime has become a universal phenomenon, meaning there is no society without any evil. Sadly crimes occurs within the scope of law enforcement itself is the police whose duty to maintain order and welfare of the community. The rise of cases of police misuse of firearms make the lack of public confidence in the Police. Criminal politics as a rational effort of society in tackling crime operationally can be done either through penal facilities or non penal means. Given the limitations / capabilities of criminal law in combating crime misuse of firearms that can not only use penal means but also using non-penal means. When viewed from the perspective of criminal politics on a macro basis, the policy of handling criminal acts of weapons misuse by using facilities outside of criminal law or non penal policy is the most strategic policy. This is because non-penal efforts are more as a precaution against the misuse of firearms. The main objective of the non-penal policy is to address and eliminate the conducive factors causing the misuse of firearms.The purpose of writing this thesis, namely: First to find out how the policy of non penal regulation of the use of firearms associated with the misuse of firearms by the Police, Second to know the weaknesses related to the regulation of the use of firearms by members of the Police linked to the misuse of firearms by the Police.Keywords: Non-Penalty-Abuse Policy-Firearms-Police Republic Indonesia